(untitled) (Global Journal of Management and Business Research, 2022)
The purpose of this article is to analyze the mediating role of the information characteristics of the management control system (MCS) in the relationship between the organizational structure and the organizational performance of companies in Cameroon, particularly those in the industrial sector. In order to better understand this study, questionnaires were administered to management controllers, financial directors and accountants of industrial companies in the cities of Douala, Yaound#xE9;, Garoua and Ngaounder#xE9;. We used structural equation modeling (MES) based on the linear structural relation method (LISREL) for the statistical analyzes. The results of this study reveal that the characteristics of CIS information (scope of information, timely and aggregated information) are the variables through which the influence of organizational structure on organizational performance passes. Therefore, industrial companies should review their management style, setting up a less centralized structure accompanied by large-scale, timely and aggregated information if they want to improve their organizational performance.